PENELITIAN AGAMA: SEBUAH CATATAN AWAL - Mufid, Mufid (Jurnal Bestari, 1991)
Sometimes, empirical approach to find the facts of world phenomena is regarded as the only one of the valid method. It will be useless when the facts of inner phenomena are the object of observation. The existence and the essence of god, for instance, cannot be observed by empirical approach. It is better for the student of religion, therefore, to use ?religion scientific? to find the facts of his observation including the ?mystical? phenomena.